PERANCANGAN SISTEM FEEDER MESIN CORRUGATED CARDBOARD SLITTER MENGGUNAKAN METODE VDI 2221 - Bryan Septiano Christly; Agus Halim; Agustinus Purna Irawan (PROSIDING SERINA, 2021)
Packaging is an integral part of a product. From all of the different variaties of packaging, cardboard packaging is the most used in different supply chains around the world. As of now, the production process in cardboard packaging industries is still heavily reliant on manual labour. To keep up with technological developments and maintain prevalence in the ever-severe market competition, automatization is the key to revolutionize the production process in cardboard packaging industries. The design of an automatic feeder for cardboard slitting process is intended as an attempt to answer those needs. To obtain an optimal result, the design process follows the method iterated in the VDI 2221 guide. The expected end-result of this design process is a finished design of the feeding system complete with detailed component specifications. The feeder design must be capable of accommodating 40 sheets of cardboard in one feeding cycle, with each sheet being 8 mm thick and weighing at most 1 kg/sheet. The obtained result of this research is a feeder design with a puller feeding system powered by a pneumatic cylinder; an adjustable platform powered by a stepper motor and a set of ballscrews. The result of this research indicates that the design has achieved its intended purpose, yet leaves room for further improvements.Kemasan merupakan bagian yang bersifat integral dari sebuah produk. Dari berbagai jenis kemasan, karton merupakan kemasan yang paling umum digunakan dalam berbagai rantai pasokan di dunia. Saat ini, proses produksi pada industri percetakan karton sangat bergantung dengan pekerjaan manual. Demi mengikuti perkembangan zaman dan mempertahankan prevalensi dalam persaingan pasar yang semakin ketat, otomatisasi merupakan kunci untuk merevolusi proses produksi pada insdutri percetakan karton. Perancangan sistem pengumpan otomatis untuk proses slitting lembaran karton merupakan suatu upaya dalam menjawab kebutuhan tersebut. Untuk mendapatkan hasil rancangan yang optimal, perancangan dilakukan dengan mengikuti panduan metode VDI 2221. Hasil akhir dari perancangan ini berupa rancangan rampung dari pengumpan dengan spesifikasi komponen yang terperinci. Rancangan harus mampu mengakomodasi 40 lembar karton dalam satu siklus pengumpanan, dengan masing-masing lembaran memiliki ketebalan sebesar 8 mm dan berat paling besar 1 kg/lembar. Hasil yang diperoleh adalah rancangan pengumpan dengan sistem pengumpanan jenis puller yang ditenagai silinder pneumatik; adjustable platform yang ditenagai motor stepper dan sepasang ballscrew. Hasil penelitian ini mengindikasikan bahwa rancangan yang dibuat telah memenuhi tujuan yang telah ditentukan, namun masih dapat dioptimasi lebih lanjut.